Yugoslav Historiography and the Civil War - Vjeran PAVLAKOVI? (Studia Historica: Historia Contemporánea, 2015)
This article examines a national historiographic tradition relatively unknown in Spain. It differs from the mainstream tradition in former Soviet bloc countries. The author first discusses the number of Yugoslav volunteers in Spain (among whom Tito was never present) and explains to Spanish readers the meaning of the Spanish Civil War with regard to the construction of a new Yugoslav identity, in the wake of Tito’s victory after the second world war and the break with Stalin. Veterans of the Spanish conflict held high positions in Tito’s Yugoslavia and contributed to maintaining the memory and meaning of their commitment. The article ends with a reference to the grotesque exploitation of several myths by both left and right-wing forces in those States resulting from the disintegration of former Yugoslavia.